Pathological significance of heme oxygenase-1 as a potential tumor promoter in heme-induced colorectal carcinogenesis - Rachitha Singhabahu; Sujani M. Kodagoda Gamage; Vinod Gopalan (Cancer Pathogenesis and Therapy, 2024)
The significance of the heme-metabolizing enzyme heme oxygenase-1 (HMOX1) in the pathogenesis of colorectal cancer (CRC) has not been fully explored. HMOX1 cytoprotection is imperative to limit oxidative stress. However, its roles in preventing carcinogenesis in response to high levels of heme are not thoroughly understood. This study reviews various mechanisms associated with the paradoxical role of HMOX1, which is advantageous for tumor growth, refractoriness, and survival of cancer cells amid oxidative stress in heme-induced CRC. The alternate role of HMOX1 promotes cell proliferation and metastasis through immune modulation and angiogenesis. Inhibiting HMOX1 has been found to reverse tumor promotion. Thus, HMOX1 acts as a conditional tumor promoter in CRC pathogenesis.